Effects of cardiac contractility modulation on autophagy and apoptosis of cardiac myocytes in rabbits with chronic heart failure. - Qingqing Hao; Shilin Lv; Jing Zhang; Huiliang Liu (PLoS ONE)
Background Cardiac contractility modulation (CCM) is non-excitatory electrical stimulation for improving cardiac function. This study aimed to evaluate the effects of CCM on autophagy and apoptosis of cardiac myocytes in a rabbit model of chronic heart failure (CHF) and explore its possible mechanism. Methods Thirty rabbits were randomised into the Sham, heart failure (HF) and CCM groups, and animals in all three groups were sacrificed after 16 weeks of ascending aortic constriction or sham surgery. The expression of autophagy associated protein LC3 was observed by immunofluorescence staining. With Western-blot measured the expression of Beclin1, P62, LC3B (II/I) and Bcl-2, ALDH2, Bax and Caspase-3 protein in myocardial tissue. The apoptosis rate and the apoptosis of myocardial cells was observed by flow cytometry and TUNEL method. Results 1) In comparison to the Sham group, the expression of LC3 and Beclin1 was significantly increased, and the expression of p62 protein was decreased in the heart tissues of rabbits in the HF group. Compared with HF group, after CCM intervention, the expression of Beclin1 and LC3B proteins decreased, while the P62 protein increased, and the LC3B(II/I) ratio decreased (P<0.05). 2) The expression of Bcl-2, ALDH2 protein and Bcl-2 mRNA decreased compared with the Sham group (P<0.05), while the expression of Bax, Caspase-3 protein and mRNA was significantly increased (P<0.05). However, the expression of ALDH2 mRNA in the CCM group was not statistically significant. The expression of Bcl-2, ALDH2 protein and mRNA increased after CCM intervention, and the expression of Bax, Caspase-3 protein and mRNA decreased (P<0.05). 3) The apoptosis situation in the Sham group was similar to that of normal myocardium, compared with the Sham group, the number of apoptotic bodies increased, and the apoptosis percentage of cardiomyocytes increased significantly (P<0.05). After CCM intervention, the number of apoptotic bodies and the percentage of apoptosis decreased compared with the HF group (P<0.05). Conclusions The intervention of CCM has been shown to enhance both myocardial systolic and diastolic function in rabbits with CHF. The mechanism may be related to the inhibition of cardiomyocyte autophagy by regulating the expression levels of Beclin1, P62, and LC3B(II/I) in cardiomyocytes, as well as the reversal of cardiomyocyte apoptosis by regulating the expression levels of Bcl-2, ALDH2, Bax, and Caspase-3 in cardiomyocytes.